2014
DOI: 10.1890/13-1687.1
|View full text |Cite
|
Sign up to set email alerts
|

Functional response of U.S. grasslands to the early 21st‐century drought

Abstract: Grasslands across the United States play a key role in regional livelihood and national food security. Yet, it is still unclear how this important resource will respond to the prolonged warm droughts and more intense rainfall events predicted with climate change. The early 21st-century drought in the southwestern United States resulted in hydroclimatic conditions that are similar to those expected with future climate change. We investigated the impact of the early 21st-century drought on aboveground net primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 56 publications
4
70
1
Order By: Relevance
“…Holden et al (2007) found the timing and intensity of precipitation events rather than precipitation totals to be the best predictors of historical variability in wildfire severity in a southwestern U.S. forest ecosystem. Similar results have been found in semiarid grassland ecosystems where metrics measuring precipitation timing, intensity, and frequency were all better predictors of overall soil moisture status and plant growth at multiple time scales (Loik et al 2004;Lauenroth and Bradford 2012;Zhang et al 2013;Hottenstein et al 2015;Moran et al 2014;Gremer et al 2015;Barnes et al 2016). Soil moisture levels are often cited as the best indicator of potential drought status given their direct connection to plant health in ecosystems and agricultural systems, fuel moisture levels, and interactions with surface and subsurface hydrological conditions, but observations are very limited, and new networks are expensive to install and maintain (Legates et al 2011;Quiring et al 2016).…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…Holden et al (2007) found the timing and intensity of precipitation events rather than precipitation totals to be the best predictors of historical variability in wildfire severity in a southwestern U.S. forest ecosystem. Similar results have been found in semiarid grassland ecosystems where metrics measuring precipitation timing, intensity, and frequency were all better predictors of overall soil moisture status and plant growth at multiple time scales (Loik et al 2004;Lauenroth and Bradford 2012;Zhang et al 2013;Hottenstein et al 2015;Moran et al 2014;Gremer et al 2015;Barnes et al 2016). Soil moisture levels are often cited as the best indicator of potential drought status given their direct connection to plant health in ecosystems and agricultural systems, fuel moisture levels, and interactions with surface and subsurface hydrological conditions, but observations are very limited, and new networks are expensive to install and maintain (Legates et al 2011;Quiring et al 2016).…”
Section: Introductionsupporting
confidence: 81%
“…These types of soil moisture-related drought impacts would be more akin to ''agricultural'' droughts, which occur on the order of months to seasons, even though the time scale of analysis is at the annual scale. The lack of systematically collected drought-impact data for the study period in this region precluded a rigorous evaluation of the type and time scale of drought impacts to which each index best relates, but studies referenced previously using similar indices lend credence that they relate to soil moisture-related impacts such as seasonal vegetation production and stress, wildfire activity, and the effectiveness of precipitation at recharging and maintaining soil moisture levels (Holden et al 2007;Dettinger et al 2011;Zhang et al 2013;Hottenstein et al 2015;Moran et al 2014). …”
Section: B Climate Extremes Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another factor that may be important are lag effects (Walker, 1993;Wiegand and Milton, 1996). Lags at short time scales, such as the effect of the previous year's precipitation, have been shown to affect plant diversity (Adler and Levine, 2007), while cover for shrubs and grasses were shown to be correlated with precipitation from two to four years previous (Anderson and Inouye, 2001) and productivity of desert grasses can take 2e4 years to recover to expected levels after drought (Moran et al, 2014).…”
Section: Introductionmentioning
confidence: 99%